The Inequality Trap & Willingness-to-Pay for Environmental Protections: The Contextual Effect of Income Inequality on Affluence & Trust. Issue 1 (2nd January 2023) - Roberts, Anthony; Mangold, Severin
ABSTRACT: Prior studies show affluence and trust increases economic support for environmental protections. However, despite widespread economic prosperity over the last two decades, variation in support for environmental protections persists across countries. We contend this variation is attributable to the growth of national income inequality which "traps" societies in environmental indifference by mitigating the effects of affluence and trust on the willingness-to-pay for environmental protections. Drawing on data from 45, 000 adult respondents in 51 countries from multiple waves of the World Value Survey, we find economic development, socioeconomic status, and trust are important determinants of a respondent's willingness-to-pay for environmental protections. More importantly, we find disposable income inequality suppresses the effects of these determinants on willingness-to-pay. Overall, the study illustrates how economic inequality contextualizes the effects of affluence and trust on environmental support which creates a barrier to widespread environmental support across countries.